1995
DOI: 10.1093/nar/23.14.2770
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human autoantibodies to transcription factor IIB

Abstract: We have characterized the ability of various human autoimmune sera to react with RNA polymerase II transcription factors. One serum, which strongly inhibited transcription in a cell-free system, was shown to contain antibodies directed against human TFIIB. The serum did not show reactivity against the other general transcription factors, including human TBP, TFIIE and TFIIF. The inhibition of transcription was directly attributable to depletion of TFIIB activity, as demonstrated by reconstitution of activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…More recently, autoantibody to TFIIB has been identified in one of 44 patients with SLE, representing 2 . 3% of patients [24]. In the present study, anti-RAP74 autoantibodies were observed in six of 153 SLE patients (3 .…”
Section: Discussionsupporting
confidence: 52%
“…More recently, autoantibody to TFIIB has been identified in one of 44 patients with SLE, representing 2 . 3% of patients [24]. In the present study, anti-RAP74 autoantibodies were observed in six of 153 SLE patients (3 .…”
Section: Discussionsupporting
confidence: 52%
“…Since autoantibodies are known to recognize subcellular complexes involved in cellular processes such as RNA splicing, RNA polymerase I11 transcript processing, and DNA replication (40), it is reasonable to consider that nuclear complexes involved in RNA polymerase I1 transcription initiation may also be recognized by autoimmune sera that contain antibodies to transcriptional activators such as Spl. The basal transcription factors, RNA polymerase I1 and TFII B, have been shown to be autoantigens (41,42), which supports the hypothesis that the RNA polymerase I1 transcription complex is autoimmunogenic.…”
supporting
confidence: 62%
“…Since autoantibodies are known to recognize subcellular complexes involved in cellular processes such as RNA splicing, RNA polymerase transcription, and ribosomal translation, it is reasonable to consider that complexes involved in these processes may also be recognized by autoimmune sera that contain antibodies to transcription factors. In several reports, RNA polymerase I [12], II [17], III [13], and TFIIB [14] have been found to be autoantigenic. Other members of the Sp1 family, except Sp1 [15] and 52-kd Ro protein, have also been reported to the autoantigenic [18].…”
Section: Discussionmentioning
confidence: 99%